The Urgency of Clinical Legal Education through Developing of Legal Aid on Campus as an Effort to Realize a Humanist Law - Winarsih, Winarsih; Cahya Wulandari (The Indonesian Journal of International Clinical Legal Education, 2019)
Legal education constitutes a fundamental pillar in the formation of law enforcement in Indonesia, yet current legal practice often reflects a rigid, rule-bound orientation that fails to adequately serve societal needs. This gap between legal norms and social realities is rooted in educational processes that emphasize theoretical knowledge over experiential learning. Although law faculties offer doctrinal courses, judicial practice modules, and internship programs, these have not been sufficient in producing graduates able to apply the law in a socially responsive and justice-oriented manner. Clinical legal education through the development of campus legal aid institutions offers a strategic solution to bridge this gap. This study examines (1) the urgency of clinical legal education within Indonesian legal education, and (2) its implementation through strengthened legal aid facilities on campus. The findings show that clinical legal education is essential for equipping students with practical competencies, deepening their understanding of community legal issues, and fostering progressive legal reasoning. Effective implementation requires expanded student engagement in community-based legal services, a shift in lecturers’ pedagogical approaches toward practice-oriented instruction, and optimization of campus legal aid institutions as laboratories for real-world legal problem-solving. These measures are expected to produce graduates capable of advancing a humanistic and justice-centered model of law enforcement.